Young adult pregnancy status and the risk of developing overweight and obesity among women and men. Issue 5 (25th July 2018) - Mamun, A. A.; McIntyre, D. H.; Najman, J. M.; Williams, G. M.; Khatun, M.; Finlay, J.; Callaway, L.
Summary: Pregnancies can end in miscarriage, birth or termination. Although it is well known that pregnancy results in weight gain across the life course, it is unknown whether pregnancies which end in termination and miscarriage contribute to this. The study used a sub‐sample of 3630 adult offspring from the original cohort of the Mater University of Queensland Study of Pregnancy (MUSP) and its outcomes, in Brisbane, Australia. Anthropometric data were measured at 5, 14 and 21 years of age and experience of pregnancy including termination, miscarriage and births were self‐reported at 21 years. Multivariable analyses were conducted to determine whether pregnancy status of young people independently associated with overweight or obesity status. The women who had at least one birth were more likely to have overweight (odds ratio [OR] 1.52; 95% confidence interval [CI]: 1.01, 2.27) or obese (OR 2.38; 95% CI: 1.58, 3.59) compared to women who did not experience any pregnancy. Women whose pregnancies were terminated or miscarried were at the same risk of overweight or obesity as women who did not experience any pregnancy. For men, there is no association between the pregnancies in their partners and the mean difference in their body mass index. Young women whose pregnancies result in a birth, but not terminations or miscarriages, are at greater risk of having overweight or obesity following the birth.